Analisis Kewirausahaan Nelayan Teripang Laut Dalam Meningkatkan Pendapatan Masyarakat - Tomy R Umar; Roy Hasiru (Universitas Negeri Gorontalo, 2022)
The purpose of the implementation of this study was to determine the entrepreneurial analysis of sea cucumber fishermen in increasing the income of the people of Torosiaje Village, Popayato District, Pohuwato Regency. This study uses qualitative methods with data collection procedures through interviews, observation and documentation. Based on the results of the research and discussion that has been carried out above, it is concluded that the entrepreneurial analysis of sea cucumber fishermen in increasing the income of the people of Torosiaje Village. Popayato District, Pohuwato Regency that village fishermen sell their sea cucumber products quickly and can cope with the daily family economy. Seeing the prospect of sea cucumbers which is a promising export commodity so that the marketing is very broad so that the existing obstacles are not so big, it's just the problem of sea cucumber stocks that are still lacking in Gorontalo. Terosaje fishermen are fish fishermen since the purchase of sea cucumbers in Torosiaje Village, the community is still not interested because they do not understand how to process them and the price of the sea cucumbers, but after starting to learn the processes from the types of sea cucumbers to the drying process and easy fishing methods, on the other hand there are collectors who are looking for sea cucumbers in large quantities at promising prices, finally tersiaje fishermen have turned to sea cucumber fishermen so that fishermen's opinions increase